O terremoto de Lisboa de 1755 e a trajetória política de Sebastião José de Carvalho e Melo - Silva, Julio Cesar da Costa (2016)
Two topics of Portuguese Modern History are of main interest to scholars, especially those studying the XVIII century: Sebastião José de Carvalho e Melo, the Marquis de Pombal, and the 1755 Lisboa Earthquake. Both are pointed as the causes of changes in Portugal history. Here, we intend to demonstrate Carvalho e Melo’s ascension until he became of the main characters of Lusitanian politics. Also, we will try to scrutinize the major political ideas behind his actions, analyzing one of his speeches, the Discurso Político sobre as Vantagens que o Reino de Portugal pode tirar de sua Desgraça por Ocasião do Terremoto do 1º de Novembro de 1755. For this, we will retrace the path of Carvalho e Melo, highlighting the main individuals and political ideas of major influence on his ideology. Last, we aim to demonstrate how, starting with the 1755 Lisboa Earthquake, Sebastião José realized that a new Portugal could rise, stronger than before.